Kantian Philosophy and Fiqh Siyar: A Hybrid Framework for Poverty Rights Protection - Subehan Khalik; Ummu Farhah Usman (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2026)
Property rights violations in conflict zones represent a critical failure of secular legal frameworks, particularly when government institutions collapse or act as perpetrators. This study proposes a novel, synthesised framework for protecting property rights in conflict zones by integrating Kantian political philosophy with Islamic jurisprudence on international relations (Fiqh Siyar). We employ a normative legal method integrated with comparative and critical analysis, proceeding sequentially to develop a philosophical-legal evaluative framework. The Kantian framework, operationalised through commitments to autonomy and dignity, provides specific indicators for protection, such as non-expropriation and effective remedies. In parallel, the analysis draws on core Islamic legal principles, including ḥifẓ al-māl (protection of wealth) and the prohibition of ghasb (unlawful seizure). Data sources are triangulated from international legal instruments, Islamic legal texts, judicial decisions, and reports from reputable organisations. The findings reveal that while Kantian philosophy emphasise institutional roles, Islamic law contributes two critical elements: an eschatological dimension of divine accountability and practical, identity-neutral legal tools for safeguarding non-combatants during systemic collapse. The study implies that effective property rights protection in such crises requires a multi-layered paradigm combining constitutional guarantees with enforceable mechanisms, strengthened by this Kantian-Islamic synthesis. This framework presents a viable alternative for contexts where traditional international law has failed, warranting further exploration for practical implementation and potential adoption by global legal institutions.